Psychosocial Assessment for Community Based Psychiatric Rehabilitation: A Practice Oriented Approach - K.J. Mathew, Mathew (International Journal of Psychosocial Rehabilitation, 2015)
community Based Rehabilitation has been recognized worldwide as a best method of rehabilitation for indi - viduals with various Psychiatric problems. It aims to restore the wellbeing and quality of life of the individuals with Psychiatric disorders at its maximum possible level with the active participation of his/her living com- munity. A comprehensive assessment of all psychosocial factors is very crucial to plan an effective manage - ment plan for any of such interventions. This article aims to give basic technical and practical information to the fresh professionals and volunteers in the field of Community Based Psychiatric Rehabilitation. The articleattempts to combine the theoretical knowledge and author’s practical experiences from the field.